Stories of Men and Teaching: A New Narrative Approach to Understanding Masculinity and Education - Davis, Ian (Springer, 2016)
This book investigates the dynamic relationship between masculinity, fiction and teaching answering one central question. How are male teachers influenced by fictional narratives in the construction of masculinities within education? It achieves this in three major steps: by describing a methodological system of narrative analysis that is able to account for the influence of a fictional text alongside a reading of interview data, by focusing on a specific cohort of male teachers in order to measure the influence of a fictional text and the literary tropes they contain, both widening and restricting perceptions of teachers and teaching. The book demonstrates how fictional narratives and their encompassing ideologies can become a powerful force in the shaping of male teachers professional identities. The book focuses on a collection of 22 fictional narratives drawn from the teacher text genre. Each text describes the world of teachers and teaching from differing perspectives, in differing forms including, literary texts; dramatic works such as plays or musicals; feature films; and television and radio series. The teacher text is a popular and prolific genre. As part of the analysis the book pilots an innovative methodological process hat reconciles the structural and textual differences between fictional texts and interview data in an effort to find points of commonality and mutual influence. Stories of Men and Teaching reveals how teaching professionals utilise tropes found in fictional texts in chaotic and unstructured ways to manage points of professional intensity as they arise. Key features such as legacy, fear, belonging, reparation and violence are identified as themes that occupy male teachers most when considering their own identity and professional performance, and each is also represented in the fictional teacher text canon.